The Effects of Psychopharmacologic and Therapeutic Approaches on Neuro-imaging in Obsessive-compulsive Disorder - Atmaca, Murad (Bentham Science Publ Ltd, 2013)
The neurobiological etiopathogenesis of OCD is still obscure. Neuroimaging studies have been very influential in shaping neurobiological models of OCD. Investigations performed within last twenty years have revealed some important findings and proposed that specific cortico-striato-thalamic circuits are involved in the mediation of its symptoms. The effects of antiobsessional drugs and cognitive behavioral therapy on structural and functional imaging have been evaluated in limited size of investigations. In structural investigations, in summary, it was found key brain regions in the pathophysiology of OCD and amygdala to change volumetrically by treatment. In functional and neurochemical investigations, by using different treatment modalities, cortico-striatal function disablements and NAA changes in a variety of brain regions were reported. In this paper, these limited data are reviewed. It is clear that there is so many things to be performed in the future researches on the effects of therapy on brains of the patients with OCD.
Keywords: OCD; Structurel; MRI; MRS; fMRI